Price of duty - Brown, Dale, 1956- (William Morrow, an imprint of HarperCollinsPublishers, 2017)
When Russia constructs its most dangerous weapon since the atomic bomb and launches carefully plotted attacks on unsuspecting U.S. and European targets, Brad McLanahan and his Scion team arm themselves with the world's most advanced technological weaponry to prevent a full-scale cyber war.